Ear Nose Throat (ENT) disorders in State Elementary Schools of Central Bali - I PUTU YUPINDRA PRADIPTHA; PURNAWAN BUDISETIA; CHRISTY ADI MUKTI (HANG TUAH MEDICAL JOURNAL, 2021)
Abstract Background: Ear, nose, and throat (ENT) health service coverage has yet to include all citizens in Central Bali. ENT disorders among elementary school-age children should be an important concern as it might affect their educational process in schools. Method: This descriptive research conducted from January to December 2019 employed a cross-sectional design. This study recruited subjects of grade 1 to 6 students from 13 elementary schools in Kubu and Tianyar village, Kubu sub-district, Karangasem district, Bali, who participated during the social service event held by Yayasan Peduli Kemanusiaan supported by Inspirasia Foundation. The total sampling method was used. Results: A number of 1115 elementary school students consisted of 578 (51.8%) male and 537 (48.2%) female students were recruited. The most and least commonly encountered ENT disorder was cerumen impaction (n=837; 75.1%) and other cases (n=8; 0.7%), respectively. Conclusion: Knowing the ENT disorders among elementary school age children in Central Bali is important as it might serve as a benchmark for conducting a precise intervention to manage ENT disorders since early age